Aplikasi Sari Akar Eceng Gondok Pada Media Murashige And Skoog (MS) Sebagai Media Multiplikasi Tanaman Krisan (Chrysanthemum morifolium Ramat, Varietan Puspita Nusantara) Secara In Vitro - Indira Pipit Miranti; Vivin Andriani (Quagga : Jurnal Pendidikan dan Biologi, 2022)
Chrysanthemum is an ornamental plant commodity that is in great demand by many people, every year the demand for chrysanthemum is increasing so that it requires the availability of good quality seeds in a sustainable manner. The use of in vitro culture techniques is one alternative that can be done. The manufacture of in vitro culture media was modified by the addition of complex organic compounds in accordance with the purpose of propagation. This study aims to determine the concentration of water hyacinth extract which effective in chrysanthemum propagation. The explants used were chrysanthemum nodes. Chrysanthemum multiplication was measured based on two parameters, total of leaves and and the length of the chrysanthemum roots. This research is a randomized complete experimental design with four different concentrations of water hyacinth root extract, concentrations SA (0%, 10%, 20%, 30%). The results showed that water hyacinth root extract had a good effect on the number of leaves and root length. On the parameter of the number of leaves, the addition of 20% water hyacinth root extract to MS medium gave the best results on the parameter of the number of leaves with an average of 13.33, while the root length parameter of MS medium as a control medium without giving water hyacinth root extract gave the highest root length results. with an average of 15.7.